PENGARUH PENYARADAN KAYU DENGAN TRAKTOR RANTAI KELABANG TERHADAP PENGGESERAN DAN PEMADATAN TANAH HUTAN - Maman Mansyur Idris; Yahya Fakuara; Gunarwan Suratmo; Rahardjo S Suparto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The study of the effect of log skidding by crawler tractors on forest soil displacement and compaction wall carried out in one logging company in West Kalimantan in 1986. The results of the study are as the following :The average volume of soil displacement was 0.06 cu.m/m of skid road, it i6 equal to 0.061 ton/sq.m. This level of soil displacement iis higher than the soil loss tolerance of 0.0002 ton/sq.m.Soil compaction as indicated by the average soil bulk density is 0.16 g/cu.cm. At this level of compaction, the porosity is 56% (far higher than 10% minimum porosity), which means that the growth of vegetation will be still favourable.The role of soil water content and slope on forest soil displacement was positively significant. The role of skidding intensity on forest soil compaction was positively significant and the role of soil water content and slope on forest soil compaction was negatively significant.